A study of variations in radial wrist extensors - Stelin Agnes Michael; Gaddam Vijaya Lakshmi (Wolters Kluwer Medknow Publications, 2019)
Background and Aim Supernumerary muscles and tendons from extensor carpi radialis longus (ECRL) and extensor carpi radialis brevis (ECRB) are sometimes encountered during hand surgery. They include accessory muscles like extensor carpi radialis intermedius (ECRI), intertendinous slips (ITS) between the two muscles, or simple birfurcated tendons. Awareness of these variations is crucial for preoperative planning for tendoplasty. This study was conducted with the aim of studying their prevalence since there is limited literature on its variations. Materials and Methods The study was carried out on 80 free upper limbs from the human cadavers, in the Anatomy Department of Pushpagiri Institute of Medical Sciences and Research Centre, Thiruvalla, Kerala. The radial carpal extensors were studied in detail. The length and width of the accessory muscles and tendons were measured. The percentage of different variations was also calculated. Results ITS from ECRL were seen in 20 of the limbs. ECRI was identified in 7 cases. Bifurcated tendon from ECRB was observed in two limbs. Absent ECRB was also noted in a specimen. In one specimen, ECRL and ECRB fused to form a single muscle and tendon, that later split into two for insertion into second and third metacarpal. The proximal attachment of both radial extensors was normal in all cases. Conclusion A total of 37.5% of variations was observed, among which supernumerary tendons accounted for 35%. Knowledge of these variations is essential in planning for tendon grafting and finger deformity correction surgeries.